HLA‐B*27:44, a novel allele identified by sequence‐based typing, is a well‐documented allele in China. Issue 3 (10th February 2013) - Gong, Z.; Zhang, Z.; Shan, X.; Mei, W.; Li, D.
<x xml:space="preserve">Abstract</x> The sequence of HLA‐B*27:44 differs in exon 2 from the sequence of B*27:08 by one amino acid change at codon 74.